Association of carotid atherosclerosis and stiffness with abdominal aortic aneurysm: The atherosclerosis risk in communities (ARIC) study. (March 2018) - Yao, Lu; Folsom, Aaron R.; Alonso, Alvaro; Lutsey, Pamela L.; Pankow, James S.; Guan, Weihua; Cheng, Susan; Lederle, Frank A.; Tang, Weihong
Abstract: Background and aims: Individuals with atherosclerosis and stiffness often have increased abdominal aortic diameters, but prospective evidence linking them to the risk of abdominal aortic aneurysm (AAA) is limited. Methods: We prospectively examined the relationship of carotid atherosclerosis and stiffness with future risk of AAA in ARIC. At Visits 1 (1987–89) or 2 (1990–1992), we assessed carotid atherosclerosis (represented by greater carotid intima-media thickness [cIMT] or presence of atherosclerotic plaque) and lower carotid distensibility (reflected by a higher carotid Beta Index). We identified incident, clinical AAAs during follow-up through 2011 using hospital discharge codes, Medicare outpatient diagnoses, or death certificates. Results: Participants' mean age at baseline was 54.2 years (SD 5.8), 45% were male and 73% white. During a median of 22.5 years of follow-up, 542 clinical AAAs were ascertained. After multivariable adjustment, the presence of carotid atherosclerotic plaque at baseline was associated with 1.31 (95% CI: 1.10–1.57; p  = 0.003) times higher risk of clinical AAA. Greater cIMT and Beta Index were also associated with clinical AAA with a dose-response across quartiles ( p trend for both: 0.006; hazard ratios [95% CI] for the highest vs. lowest quartiles: 1.55 [1.13–2.11] and 1.68 [1.16–2.43], respectively). The associations of cIMT and Beta Index with AAA were independent of each other. Conclusions: This prospective population-based study found that indices of greater carotid atherosclerosis and lower carotid distensibility are markers of increased AAA risk. Highlights: Findings of this report were based on a large, population-based cohort study with more than 20 years of follow-up. Carotid atherosclerosis was associated with increased risk of clinical abdominal aortic aneurysms (AAA). Low carotid distensibility was also associated with increased risk of clinical AAA.